Une spiritualité féminine hors institution ? L’Histoire de la vie et mœurs de Marie Tessonnière (1650) - Antoinette GIMARET (E-REA)
The biography of Marie Tessonnière, known as Marie de Valence (15761648), was published in 1650 by Father Louis de la Rivière; it offers an interesting example of the ambivalent relationship of female spirituality with early modern institutions, and of the contradictions to be found in the genre of spiritual biography. This article shows how the author of the text, whilst recognising Marie’s exceptionality as a potential source of scandal, endeavours to place her within the hagiographic field. It then questions the gendered dimension of the enterprise and La Rivière’s valorisation of a real female apostolate, which somewhat complicated the reception of the text in 1650 and justified the censorship with which it was met.